Dampak Asuransi Kesehatan dan Kredit Mikro terhadap Masalah Kesehatan dan Konsumsi Rumah Tangga : (Studi Kasus di Kota Kupang Provinsi Nusa Tenggara Timur) - Muhammad Liwaulhamdi; Maria I. Hewe Tiwu; Fransina W. Ballo; Novi Theresia Kiak (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the role of health insurance and micro-credit in overcoming the impact of health shocks on household consumption in Kupang City. The research method used is a case study with a qualitative descriptive approach. Primary data were obtained through in-depth interviews with BPJS Kesehatan, Obor Mas Savings and Loans Cooperative, and beneficiary communities. The results of the study indicate that health insurance significantly reduces the financial burden due to health problems, while micro-credit provides alternative financing solutions that maintain the stability of household consumption. These findings emphasize the importance of synergy between health insurance and microfinance access to improve household economic resilience in facing health risks.